Significance of serum electrolyte imbalance and comparison between different testing methods in patients with altered sensorium presenting to tertiary care hospital - Dumra, Harjit S.; Patel, Kautuk A.; Raval, Gopal; Dandnaik, Mansi; Patel, Amrish (International Journal of Advances in Medicine, 2019)
Background: Electrolyte disorders are common in patients in the emergency department and intensive care unit, and have been associated with increased morbidity and mortality. In this respect sodium and potassium are the most important cations, whose improper adjustment may cause severe neuromuscular disorders. This study was designed to compare values obtained by laboratory and point-of-care testing and also to find most frequent electrolyte abnormalities. Methods: Observational Study was done on 51 patients presenting to Tertiary care Hospital emergency department with altered sensorium between 1st January 2016 to 31st May 2017 fulfilling the inclusion criteria and willing for participation by giving written informed consent. Electrolytes were tested in patients with GCS 14 or less by both point of care system and in the laboratory. Results: The distribution of mean sodium and potassium levels did not differ significantly between two techniques (P-value>0.05). The sodium and potassium levels by POC and laboratory techniques are significantly and positively correlated (P-value<0.001). The distribution of mean along with 95% CI of mean of amount of bias in the estimation of Sodium and Potassium levels by POC against Laboratory method is 3.50 [2.79-4.20] mEq/L and 0.83 [0.55-1.11] mEq/L respectively. The most common electrolyte abnormality was hyponatremia. Conclusions: We concluded that it is advisable to do a point-of-care electrolyte in Emergency department and Intensive care unit. By use of point-of-care testing, we can identify electrolytes imbalance early in emergency department. Point-of-care electrolyte levels had a near comparable value with laboratory electrolyte levels.